Differences In Learning Concentration of Students Taught with Whiteboard Animation Media - Ganefri; Giatman; Prasetya, Febri; Yulastri, Asmar; Efendi, Hansi; Muskhir, Mukhlidi (The Indonesian Journal of Computer Science, 2023)
This study originated from the lack of enthusiasm of students following the learning of milling machining in the classroom, because of the many distractions that make it difficult for students to concentrate. The purpose of this study is to determine whether there is a difference in students' learning concentration in the subject of milling machining techniques of vocational high school students when they are taught with whiteboard animation media and textbooks. This research design is a quasi-experiment with post-test only. Based on the researcher's consideration and initial interviews, the subjects of this study were formulated as two classes. The number of students for the experimental class XI TPM 1 (15 people) and the conventional class XI TPM 2 (15 people). The experimental class XI TPM 1 was given whiteboard animation learning media, while the conventional class XI TPM 2 was given conventional learning. To analyze the research data, t-test technique was used. The results of the t-test analysis showed that, compared to the conventional learning method, students learned milling machining techniques with higher concentration.